2009
DOI: 10.1002/hon.877
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell CD38 expression in B‐chronic lymphocytic leukaemia

Abstract: B-cell chronic lymphocytic leukaemia (B-CLL) is a heterogeneous disease with some patients having an indolent course never needs treatment, while others having rapidly progressive one requires intensive treatment. In recent decades, numerous prognostic markers, such as immunoglobulin variable region heavy-chain (IgVH) mutational status, ZAP-70 and the expression of CD38 on leukaemic cells were introduced to screen for patients likely to have progressive course of B-CLL bearing the potential to facilitate risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…CD38 expression on T cells has been shown to reflect chronic activation and stimulation in various diseases [32, 33] and also in acute graft rejection [34]. Our own group has recently shown that the levels of CD38 expression on T cells predict the course of the disease in male CLL patients with higher CD38 expression correlating with a worse clinical prognosis [35], and this was confirmed by the recent study by Abousamra et al [36]. According to these data, CD38 + T cells, despite their activated phenotype, seem to fail to perform sufficient tumour control in CLL but rather support maintenance or even expansion of the malignant clone.…”
Section: Discussionmentioning
confidence: 70%
“…CD38 expression on T cells has been shown to reflect chronic activation and stimulation in various diseases [32, 33] and also in acute graft rejection [34]. Our own group has recently shown that the levels of CD38 expression on T cells predict the course of the disease in male CLL patients with higher CD38 expression correlating with a worse clinical prognosis [35], and this was confirmed by the recent study by Abousamra et al [36]. According to these data, CD38 + T cells, despite their activated phenotype, seem to fail to perform sufficient tumour control in CLL but rather support maintenance or even expansion of the malignant clone.…”
Section: Discussionmentioning
confidence: 70%
“…9,16 Additionally, T-cell expression of CD38 has been shown to be important in a number of diseases, 41–43 such that imaging of this target in humanized mice 44 may provide insight into the behavior of T-cells and their homing to tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinically, this PET tracer may find application in a wide variety of malignancies in which CD38 expression has been correlated with patient outcomes in order to better understand disease progression. , Additionally, T-cell expression of CD38 has been shown to be important in a number of diseases, such that imaging of this target in humanized mice may provide insight into the behavior of T-cells and their homing to tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore tempting to speculate that peculiar biological features of the residual T cell component in CLL, as it could be identified by the variable expression of specific markers, e.g. CD38, telomeres, CD25 and CD54 [41-45] or, as shown here, ZAP-70, might be the result of interactions of T cells themselves with CLL cells, which might eventually contribute to define the clinical features of the disease [40,46]. …”
Section: Discussionmentioning
confidence: 99%